Childhood obesity: Impact, outcome and preventive strategies - Mohan T. Shenoy; Vineetha K. Ramdas Nayak (Elsevier, 2023)
Childhood Obesity is a major public health issue. There is a rising trend in global community due to rapid urbanization and reduced physical activity. This review explores the pathophysiology, clues for screening and early recognition of this alarming problem. It is important to develop cost-effective strategies in liaison with the school authorities, parents, and healthcare professionals.